Northern Bobwhite and Fire: A Review and Synthesis - David A Weber; Evan P Tanner; Theron M. Terhune II; J. Morgan Varner; James A. Martin (National Quail Symposium Proceedings, 2022)
Our understanding of the relationship between northern bobwhite (Colinus virginianus; hereafter, bobwhite) and fire began with Herbert Stoddard’s work in the early 20th century. Research on the topic has continued, but our application of fire is deeply rooted in Stoddard’s work, even as it has become evident that fire regimes must be adapted to variable environmental conditions that are evolving with a changing landscape and climate. A comprehensive review and synthesis of the literature on this topic would help formalize research advancements since Stoddard and identify knowledge gaps for future research. Results from experiments suggest fire creates favorable local habitat conditions for bobwhite such as plant composition, bare ground, and plant structure. Frequent prescribed fire is closely tied to where bobwhite populations are at their greatest (e.g., Red Hills region of Georgia and Florida, USA). However, an empirical gap exists between patch-level conditions and the bobwhite-landscape ecology interface. For example, it is well established that a 2-year fire return interval in pine savanna ecosystems with fertile soil is best for bobwhite. But causal evidence is limited for areas of different soil types, precipitation, and past land use across the bobwhite range. We review the extant literature describing prescribed fire use for bobwhite management, focusing on documented effects of fire on life-history characteristics of bobwhite under different environmental conditions. Habitat outcomes of fire management depend on fire frequency, seasonality, scale, and interaction with other management, and different strategies should be employed depending on the environment and desired effects. Adaptive management strategies will be necessary to address the challenges of rising temperatures associated with a changing climate, which are likely to alter the conditions under which burns occur and increase the difficulty of meeting basic burn criteria. Positive public attitudes toward prescribed fire will be key to developing a policy and management framework that supports efficient prescribed fire application. Our review elucidates range-wide processes and patterns to better inform the site-specific application of fire.
Keywords: climate change; Colinus virginianus; Great Plains; habitat management; life history; northern bobwhite; pine savanna; policy